Materiality Decisions and the Correction of Accounting Errors - Acito, Andrew A.; Burks, Jeffrey J.; Johnson, W. Bruce (The Accounting Review, 2009)
ABSTRACT: We test conjectures about the determinants of materiality judgments by examining a financial reporting choice made by firms that discover errors in prior years' financial statements. From late 2004 to mid-2006, more than 250 U.S. firms uncovered and corrected operating lease accounting errors either by formal restatement—required for errors deemed material—or by a less visible current-period “catch-up” adjustment. We test the role of materiality considerations outlined in SAB No. 99 as well as factors outside authoritative guidance in explaining the correction method chosen. Although both quantitative and qualitative materiality considerations cited in the guidance explain a large portion of the variation in firms' error correction decisions, we find that the prior actions of other firms also appear to play a major role. We also find that clerical considerations, but not strategic disclosure concerns, help explain cross-sectional variation in the timing of firms' error correction announcements.